Talent management innovations in the international hospitality industry - Jooss, Stefan; Burbach, Ralf; Ruël, Huub (Talent management., 2021)
The hospitality industry relies on the sourcing and development of talent to deliver excellent customer experiences and interactions in a 24/7 environment. Talent Management Innovations in the International Hospitality Industry explores both research and practical perspectives on contemporary talent management, presenting a diverse range of stakeholder views in a variety of international hospitality settings. This collection circumnavigates a wide range of subjects within the talent management field, including employer branding, creative talent, talent pools, and mentoring initiatives, along with a focus on talent identification, development, and retention. The new insights aid academics and professionals in gaining a greater understanding of the multifaceted nature of talent management in this people-centric industry and offers a comprehensive set of evidence-based research and practical examples of talent management innovation in the international hospitality industry.